Chemical safety and security after Beirut Port explosion: Part1 - State of the art of legal framework and authorization policy. (December 2021) - Malak, Fadi; Rifai, Ahmad; Baydoun, Rana; Nsouli, Bilal; Dimitrov, Dimitar
Highlights: Beirut Port explosion (04 August 2020), and its disastrous consequences urge the shedding of light on the national legal framework governing the practices involving chemical materials in Lebanon. Management of chemical and dual use materials used at several sectors Lebanon. Implementation of international treaties and conventions specially those related to chemical safety and security issues. Weakness and suggestions for upgrading the current related legal and administrative system. Abstract: In the fourth of August 2020, around 2750 tons of ammonium nitrate stored in a warehouse at Beirut Port were exploded causing about 220 deaths and 6500 injuries, in addition to the displacement of 300, 000 Lebanese citizens from their destroyed homes. The disastrous consequences of this blast at social, economic, security and political scales, earned great interest at national, regional and international levels. The explosion caused severe stagger to the Lebanese Government that resign after few days. The catastrophic event urged to shed the light on the legal texts and international treaties and conventions that governs the use of chemical materials specially the hazardous ones. This paper aims to highlight the current legal framework and the implementation of relevant international conventions, specially the Chemical Weapons Convention, in managing the import, use and storage of hazardous materials in Lebanon, through deep review of available national texts that governs the work and roles of concerned ministries and institutes. This study will be considered as a basement for a gap analysis that need to be undertaken for enhancing chemical safety and security in the country by strengthening the used procedures for import, export and trade and to poster interagency coordination scheme since the practices cited above are decisions related to different national stakeholders (Ministries of Environment, Industry, Defense, Interior and Municipalities, Trade and Economy, Public Health, Agriculture and security institutes).